2014
DOI: 10.4236/psych.2014.515184
|View full text |Cite
|
Sign up to set email alerts
|

Self-Motion Perception Induced by Cutaneous Sensation Caused by Constant Wind

Abstract: We first in the history of vection research, challenged to induce cutaneous vection by providing the participants body with wind. Participants wore an eye mask to block out all outside visual information, and white noise was presented through a pair of earphones to block out all outside auditory information. We also provided body sway by using a horse-riding machine. The constant wind was provided to the participants from the front, side and behind of them. The results clearly showed that the cutaneous vection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Given that there is no inherent visual connotation in the Latin root of the word, it is perhaps no surprise that ‘vection’ is now increasingly being used to also refer to illusory self-motions induced by stimulating the non-visual self-motion senses . These non-visual illusions of self-motion (where the observer is typically either seated in darkness or blindfolded) include: (1) Auditory vection – illusory self-motion induced by moving the observer’s acoustic surround ( Dodge, 1923 ; Lackner, 1977 ; Sakamoto et al, 2004 ; Riecke et al, 2008 ; Keshavarz et al, 2014 ; see Väljamäe, 2009 for a review); (2) Haptokinetic vection – illusory self-motion produced by applying tactile motion stimulation to large areas of the observer’s body ( Dichgans and Brandt, 1978 ; Nilsson et al, 2012 ; Nordahl et al, 2012 ; Murata et al, 2014 ); (3) Arthrokinetic vection – illusory self-motion induced by passively rotating the observer’s limb/s ( Brandt et al, 1977 ; Howard et al, 1998 ); and (4) Biomechanical vection – illusory self-motion generated when a standing/seated subject repeatedly steps on a treadmill ( Bles, 1981 ; Riecke et al, 2011 ). Interestingly, while illusions of self-motion can also be induced by caloric (e.g., Fasold et al, 2002 ) and direct galvanic stimulation (e.g., Cress et al, 1997 ; Lepecq et al, 2006 ), such vestibular illusions are rarely referred to as vestibular vection (see below for one notable exception) 2 .…”
Section: Challenge 1: Defining Vectionmentioning
confidence: 99%
“…Given that there is no inherent visual connotation in the Latin root of the word, it is perhaps no surprise that ‘vection’ is now increasingly being used to also refer to illusory self-motions induced by stimulating the non-visual self-motion senses . These non-visual illusions of self-motion (where the observer is typically either seated in darkness or blindfolded) include: (1) Auditory vection – illusory self-motion induced by moving the observer’s acoustic surround ( Dodge, 1923 ; Lackner, 1977 ; Sakamoto et al, 2004 ; Riecke et al, 2008 ; Keshavarz et al, 2014 ; see Väljamäe, 2009 for a review); (2) Haptokinetic vection – illusory self-motion produced by applying tactile motion stimulation to large areas of the observer’s body ( Dichgans and Brandt, 1978 ; Nilsson et al, 2012 ; Nordahl et al, 2012 ; Murata et al, 2014 ); (3) Arthrokinetic vection – illusory self-motion induced by passively rotating the observer’s limb/s ( Brandt et al, 1977 ; Howard et al, 1998 ); and (4) Biomechanical vection – illusory self-motion generated when a standing/seated subject repeatedly steps on a treadmill ( Bles, 1981 ; Riecke et al, 2011 ). Interestingly, while illusions of self-motion can also be induced by caloric (e.g., Fasold et al, 2002 ) and direct galvanic stimulation (e.g., Cress et al, 1997 ; Lepecq et al, 2006 ), such vestibular illusions are rarely referred to as vestibular vection (see below for one notable exception) 2 .…”
Section: Challenge 1: Defining Vectionmentioning
confidence: 99%
“… 2 Auditory (e.g., Keshavarz et al., 2014 ; Mursic, Riecke, Apthorp, & Palmisano, 2017 ; Väljamäe, 2009 ) and tactile (e.g., Murata et al., 2014 ; Nordahl, Nilsson, Turchet, & Serafin, 2012 ) motion stimulation have both been reported to produce similar (although often less compelling) illusions of self-motion in blindfolded observers. Illusory self-motion can also be induced by passively rotating the limbs of blindfolded observers (e.g., Howard, Zacher, & Allison, 1998 ) or having them step on a treadmill (e.g., Bles, 1981 ).…”
mentioning
confidence: 99%
“…In our study, the participants in the Water condition had the somatosensory input from the water moving around their body. In this way, the water could have played a similar role than the wind previously used in studies 23 , 24 and induced greater vection than in the Ground condition. Although in our case, it needs to be highlighted that the water movement was not directional.…”
Section: Discussionmentioning
confidence: 89%
“…They found that participants experiencing visual and somatosensory motion cues experienced greater vection than participants experiencing visual cues only. Murata and colleagues 24 combined somatosensory and proprioceptive systems while blindfolding the participants to avoid visual cues. The participants were seated on a horse-riding machine and swayed back and forth while directional wind was blowing on their whole body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation